2020
DOI: 10.3390/ijerph17020617
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation and Functional Decline: A Comparative Study of Rural and Urban Older People, Using Japan Gerontological Evaluation Study Longitudinal Data

Abstract: This study compared the relationship between social participation, including work, and incidence of functional decline in rural and urban older people in Japan, by focusing on the number and types of organizations older people participated in. The longitudinal data of the Japan Gerontological Evaluation Study (JAGES) that followed 55,243 individuals aged 65 years or older for six years were used. The Cox proportional hazards model was employed to calculate the hazard ratio (HR) of the incidence of functional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…11 For example, Kanamori et al, 10 found that older people who participated in one group demonstrated a 0.83 times lower incidence of disability, while those who participated in two groups demonstrated a 0.72 times, and those who participated in three or more different types of groups demonstrated a 0.57 times lower risk of disability than those who did not participate in any group. Similarly, Ide et al 8 reported that the number of groups an older adult participated in was associated with lowered risk of functional decline in both rural and urban areas (0.76-0.92 times lower risks than those who did not participate in any group). Furthermore, compared with the active participant group (ie, exercising once a month or more, and participation in a sports organization), the sedentary group (ie, exercising less than once a month and no participation in a sports organization) exhibited a 1.65 times increase in risk, while the exercise-alone group (ie, exercising once a month or more and no participation in a sports organization) demonstrated a 1.29 times increased risk for incidence of functional disability.…”
Section: Indirect Negative Health Impacts Of Covid-19 On Older Peoplementioning
confidence: 93%
See 1 more Smart Citation
“…11 For example, Kanamori et al, 10 found that older people who participated in one group demonstrated a 0.83 times lower incidence of disability, while those who participated in two groups demonstrated a 0.72 times, and those who participated in three or more different types of groups demonstrated a 0.57 times lower risk of disability than those who did not participate in any group. Similarly, Ide et al 8 reported that the number of groups an older adult participated in was associated with lowered risk of functional decline in both rural and urban areas (0.76-0.92 times lower risks than those who did not participate in any group). Furthermore, compared with the active participant group (ie, exercising once a month or more, and participation in a sports organization), the sedentary group (ie, exercising less than once a month and no participation in a sports organization) exhibited a 1.65 times increase in risk, while the exercise-alone group (ie, exercising once a month or more and no participation in a sports organization) demonstrated a 1.29 times increased risk for incidence of functional disability.…”
Section: Indirect Negative Health Impacts Of Covid-19 On Older Peoplementioning
confidence: 93%
“…Third, while social gatherings increase the risk of spreading the coronavirus, the benefits of social participation should also be taken into account. Using data from JAGES, various studies have presented the relationships between increased social participation and health, such as a decreased risk of dementia, 4 , 5 and cognitive impairment, 6 increased instrumental activities of daily living scores, 7 decreased incidence of functional disability, 8 - 11 and death. 11 For example, Kanamori et al, 10 found that older people who participated in 1 group demonstrated a 0.83 times lower incidence of disability, while those who participated in 2 groups demonstrated a 0.72 times, and those who participated in 3 or more different types of groups demonstrated a 0.57 times lower risk of disability than those who did not participate in any group.…”
Section: Indirect Negative Health Impacts Of Covid-19 On Older Peoplementioning
confidence: 99%
“…Participants reported their frequency of participation in each type of organization by choosing one of the following response options: four times or more per week, two to three times per week, once a week, one to three times per month, several times per year, and never. The response was categorized as “yes” if the participants answered “several times per year or more” and “no” if they answered “never” [ 24 ]. Involvement in various types of social activities was counted and classified from 5 (participation in all) to 0 (no participation).…”
Section: Methodsmentioning
confidence: 99%
“…A study on urban and rural differences in China found that older adults in rural areas had higher levels of depression than those in urban areas [ 14 ]. According to a study comparing urban and rural Japan, older adults in rural areas display lower social participation and higher dementia risk than those in urban areas [ 15 , 16 ]. Moreover, depression is one of the factors of dementia in older adults [ 1 ].…”
Section: Introductionmentioning
confidence: 99%